Preparing Human Resources for Global Competition - Hudtohan, Emiliano T. (International Journal of Management and Education in Human Development, 2024)
This lecture is intended for the business graduate school students who will eventually find themselves as human resources in a corporate work environment in the 21st century. The New Year 2024 ushers the end of a Great Period of Change (2012-2023) in a volatile, uncertain, complex, and ambiguous (VUCA) world and the Age of Upheaval in business, where our human condition, according to Br. Armin Luistro, FSC, is Finite, Fragile and Free. For the new graduate, being antifragile means resilience in facing daunting challenges and being an agent who strives for total development to meet challenges with personal diligence to achieve avowed short- and long-term goals for corporate survival. More importantly, it is critical for the new graduate to realize that s/he is an empowered individual who is 99.999 percent spirit and .001 percent body, described as such by quantum physicists: Bruce Lipton, Sean Carroll, Joe Dispenza, James Ray and Neale Donald Walsch. The graduate is therefore encouraged to create a Personal Vision and Mission, using Alan Seale’s meditation formula and craft her/his true purpose and strategic life direction anchored to the supernatural, metaphysical, and physical/natural realities of human experience. In corporate practice, the graduate may encounter two leadership style: a manager-centered leader described in Managerial Grid or employee-centered leader in Situational Leadership.